Experimental and Numerical Studies on the Explosion Characteristics of Ethanol–Air Mixtures under Aviation Conditions - Xiaoyao Ning; Zhihui Zhang; Kangxue Zheng; Xuehui Wang; Jian Wang (Fire, 2023)
As a representative renewable biofuel, ethanol can reduce mankind’s dependence on petroleum resources and the emission of greenhouse gases and other pollutants. In recent years, the application of ethanol in the aviation field has begun to be a concern of scholars. As ethanol is a flammable liquid, it is significant to study its explosion characteristics in aviation conditions from a safety perspective. In this work, at 20 kPa, the explosion characteristics of ethanol–air mixtures (concentration 6~12%) were experimentally and numerically studied under an initial temperature range of 303 K~363 K. The effects of the initial temperature and concentration on the maximum explosion pressure, maximum rate of pressure rise, explosion time, and fast burning time were analyzed. In addition, the heat loss fraction and sensitivity analysis were examined and discussed. The main conclusions are as follows: A linear relationship exists between the maximum explosion pressure and the reciprocal of the initial temperature. The maximum rate of a pressure rise appears to decrease or at least approach a constant value as the initial temperature increases. The explosion time is significantly dependent on the concentration. At a constant concentration, the proportions of heat loss are approximately constant except for 12%. In our sensitivity analysis, R1 (H + O2 <=> O + OH) was the dominant elementary reaction.